PENERAPAN METODE PEMBELAJARAN EVERYONE IS A TEACHER HERE TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 1 BANUHAMPU - Tiara Fikriani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2017)
This study aims to determine the effect of the method everyone is a teacher here on the results of students mathematics learning in class VIII SMP Negeri 1 Banuhampu. Type of this research is correlational study aimed to detect the extent of variations on a factor related to variations in one or more other factors based on the correlation coefficient. The population in this study were students of class VIII SMP Negeri 1 Banuhampu with class VIII6 drawn as a sample. The hypothesis of this study is the learning method everyone is a teacher here affect the results of students' mathematics learning in SMP Negeri 1 Banuhampu. Based on data obtained normality test using Lilliefors test, turned out of the normality test conducted on an error from the distribution of X and Y have normal distribution of data distribution. Further analysis of correlation coefficients and coefficients of determination turns obtained correlation (r) is 0.97, while the coefficient of determination (r 2) is 0.9409 where Based on testing criteria are very positive correlation. This means that 94.09% of hypothesis testing is accepted at the level of 95%. Last to perform hypothesis testing, calculations obtained t = 21.487 & gt; table = 2.042 which means that the hypothesis is accepted. So based on the calculation results are very positive influence learning methods everyone is a teacher here. Based on the results of class VIII student of SMP Negeri 1 Banuhampu acceptable at a level of 95%.